Cholesteric Liquid Crystalline Copolymers for Gas Chromatographic Separation of Polycyclic Aromatic Compounds - Chih-Hung Lin (Advances in Materials Science and Engineering)
A novel series of side-chain liquid crystalline copolysiloxanes containing [S]-1-(2-naphthyl) ethyl 6-[4-(10-undecen-1-yloxy) biphenyl--carbonyloxy]-2-naphthoate mesogenic and 4-biphenyl -allyloxybenzoate mesogenic side groups in the backbone and side chains liquid crystalline copolymers were prepared and evaluated as possible stationary phases for gas chromatography capillary columns. All copolymers display enantiotropic cholesteric phases. These mesomorphic polysiloxanes specimens with the widest temperature range were used as the stationary phase in a gas chromatography capillary column, and it showed good thermal and physical stability, excellent chemical inertness, and unique separation properties for polycyclic aromatic compounds. These cholesteric LC copolysiloxane stationary phases show much better separation effect for the polycyclic aromatic compound than those of the nematic and smectic LC copolysiloxanes.